Long-Term Oncologic Outcomes After Laparoscopic and Robotic Tumor Enucleation for Renal Cell Carcinoma - Dong, Wen; Chen, Xiong; Huang, Ming; Chen, Xu; Gao, Ming; Ou, Dehua; Li, Kaiwen; Wang, Chenyang; Wu, Shaoxu; Liu, Hao; Xie, Weibin; Xie, Wenlian; et al. (Frontiers in Oncology, 2021)
Objectives: Tumor enucleation (TE) optimizes parenchymal preservation with promising short-term oncologic outcomes compared with standard partial nephrectomy (SPN). However, researches/literatures about long-term oncologic outcomes for TE after minimally invasive surgery are scarce. We aim to analyze long-term oncologic outcomes after laparoscop-ic and robotic tumor enucleation for renal cell carcinoma (RCC). Patients and Methods: We retrospectively analyzed 146 patients who underwent TE with either laparoscopic or robotic approach for localized RCC in our center. Local recurrence, cancer specific survival (CSS), re-currence free survival (RFS) and overall survival (OS) were the main out-comes. Survival curves were generated using a Kaplan-Meier method. Perioperative outcomes and pathological outcomes were also analyzed. Results: Overall, 98 male and 48 female patients were eligible for the study. The median tumor size was 3.4cm with a median R.E.N.A.L. score of seven. Warm ischemia was used in 143 patients with a median ischemia time of 20 minutes and three patients had zero ischemia. Five patients (3.4%) had major complications (> Clavien IIIa) and only two were relat-ed to urinary system. The median global glomerular filtration rate (GFR) preserved after surgery was 93%. Pseudocapsule invasion was reported in 50 tumors (34%) and positive surgical margins were found in 3/146 (2.1%) tumors. At a median follow-up of 66 months, local recurrence happened in two patients (1.4%), and systemic recurrence happened in six patients (4.2%). The 5-year CSS, RFS, OS were 95.7%, 89.6% and 91.9%, and the 10-year CSS, RFS, OS were 93.8%, 89.6% and 90.0%, respectively. Conclusion: This study indicates that tumor enucleation with laparoscop-ic or robotic approach in experienced hands for the treatment of RCC ap-pears oncologically safe with a median follow-up of more than five years. Prospective studies with more patients and longer follow-up will be re-quired to further evaluate oncologic safety after TE.